2017
DOI: 10.1021/acsenergylett.7b00110
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ionic Liquid Electrolyte in an Aluminum–Graphite Electrochemical Cell

Abstract: Using first-principles calculations and molecular dynamics simulation, we study the working mechanism in an aluminum–graphite electrochemical cell, which was recently reported to exhibit attractive performance. We exclude the possibility of Al3+ cation intercalation into graphite as in standard Li-ion batteries. Instead, we show that the AlCl4 – anion intercalation mechanism is thermodynamically feasible. By including the ionic liquid electrolyte in the overall redox reaction, we are able to reproduce the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 42 publications
(88 reference statements)
6
76
0
2
Order By: Relevance
“…A further excellent study by Agiorgousis et al. demonstrated similar reaction mechanisms with regard to the fast intercalation and diffusion of AlCl 4 − and the high operating voltage of the Al‐graphite cell using the AlCl 3 /[EMIM]Cl electrolyte, according to the results of first‐principles calculations and molecular dynamics simulation . Similar reaction mechanisms for the graphite cathodes have also been proposed when the AlCl 3 /organic solvent eutectic electrolyte or inorganic AlCl 3 /alkali chloride eutectic electrolyte was used .…”
Section: Alcl3‐based Electrolytes For Aluminum Batteriesmentioning
confidence: 57%
See 1 more Smart Citation
“…A further excellent study by Agiorgousis et al. demonstrated similar reaction mechanisms with regard to the fast intercalation and diffusion of AlCl 4 − and the high operating voltage of the Al‐graphite cell using the AlCl 3 /[EMIM]Cl electrolyte, according to the results of first‐principles calculations and molecular dynamics simulation . Similar reaction mechanisms for the graphite cathodes have also been proposed when the AlCl 3 /organic solvent eutectic electrolyte or inorganic AlCl 3 /alkali chloride eutectic electrolyte was used .…”
Section: Alcl3‐based Electrolytes For Aluminum Batteriesmentioning
confidence: 57%
“…[283] Them inimum energy barrier of the AlCl 4 À cluster is about one order of magnitude lower than that of Li migration in graphite.I n addition, the tetrahedral AlCl 4 À cluster will distort and prefers to be in the form of ap lanar quadrangle when it is intercalated in bulk graphite, [284] in which the interlayer spacing was expanded from 3.35 to 6.02 .T his finding is consistent with the work of Dai et al [25] Af urther excellent study by Agiorgousis et al demonstrated similar reaction mechanisms with regard to the fast intercalation and diffusion of AlCl 4 À and the high operating voltage of the Al-graphite cell using the AlCl 3 /[EMIM]Cl electrolyte,a ccording to the results of first-principles calculations and molecular dynamics simulation. [285] Similar reaction mechanisms for the graphite cathodes have also been proposed when the AlCl 3 /organic solvent eutectic electrolyte or inorganic AlCl 3 /alkali chloride eutectic electrolyte was used. [213,238] Kravchyk et al used 27 Al NMR spectroscopy to directly reveal the AlCl 4 À intercalation in graphite.…”
Section: Angewandte Chemiementioning
confidence: 63%
“…[4][5][6][7][8][9][10] Now,w hen we talk about cathodes, numerous cathode materials have been examined for Al batteries, which can reversibly intercalate and deintercalate AlCl 4 À during charging and discharging reactions, respectively. [11][12][13][14][15][16][17][18][19] Experimentally,different studies have been executed for Al batteriesc athode by diversifying the graphite at structural level, such as naturalg raphite, [1,9] graphite foam, [20] graphitic carbon paper, [8] few layered graphene sheets, [21,22] polypyren [23] etc. These structural variations have definitely improved the overall performance of Al batteries in terms of increased voltage, higherc yclel ife and better storage.…”
Section: Introductionmentioning
confidence: 99%
“…Eine weitere exzellente Arbeit von Agiorgousis et al. zeigte ähnliche Reaktionsmechanismen in Bezug auf die schnelle Interkalation und Diffusion von AlCl 4 − und die hohe Arbeitsspannung der Al‐Graphit‐Zelle mit dem AlCl 3 /[EMIM]Cl‐Elektrolyten, wie First‐Principles‐Rechnungen und Molekulardynamik‐Simluation ergaben . Vergleichbare Reaktionsmechanismen für die Graphitkathoden wurden auch vorgeschlagen, als AlCl 3 /organisches Lösungsmittel oder anorganisches AlCl 3 /Alkalimetallchlorid als eutektische Elektrolyte verwendet wurden .…”
Section: Alcl3‐basierte Elektrolyte Für Aluminiumbatterienunclassified
“…Außerdem wird sich der vierflächige AlCl 4 À -Cluster verformen und ist in der Form eines flachen Vierecks,w enn es in Graphit interkaliert ist, [284] in welchem der Abstand der Zwischenschichten von 3.35 zu 6.02 expandiert wurde.D iese Feststellung ist konsistent zur Arbeit von Dai et al [25] Eine weitere exzellente Arbeit von Agiorgousis et al zeigte ähnliche Reaktionsmechanismen in Bezug auf die schnelle Interkalation und Diffusion von AlCl 4 À und die hohe Arbeitsspannung der Al-Graphit-Zelle mit dem AlCl 3 /[EMIM]Cl-Elektrolyten, wie First-Principles-Rechnungen und Molekulardynamik-Simluation ergaben. [285] Vergleichbare Reaktionsmechanismen fürd ie Graphitkathoden wurden auch vorgeschlagen, als AlCl 3 /organisches Lçsungsmittel oder anorganisches AlCl 3 /Alkalimetallchlorid als eutektische Elektrolyte verwendet wurden. [213,238] Kravchyk et al zeigten direkt die AlCl 4 À -Interkalation in Graphit mittels 27 Al-NMR-Spektroskopie.…”
Section: Chloraluminat-anionen-transferunclassified